Correlation of kinesiophobia and upper extremity parameters in post mastectomy patients - Aleem, Hijab; Rimsha Qazi; Muhammad Ehab Azim; Maria Ismail; Humna Amer; Madiha Ashfaq (Journal of the Pakistan Medical Association, 2023)
Breast cancer, if diagnosed at advanced stages, often leads to surgical intervention, i.e. mastectomy, which later presents complications that add to morbidity. A cross-sectional analytical study was conducted to determine pain, upper limb ROM, grip strength, lymphoedema, and their co-relation with kinesiophobia in post mastectomy patients. A sample of 55 female patients was selected via non-probability purposive sampling. Kinesiophobia was assessed using Tampa Scale of kinesiophobia (TSK-11) and pain via Numeric Pain Rating Scale. Upper extremity ROM was measured using a plastic goniometer, grip strength by Jamar Hydraulic dynamometer, and limb volumes were calculated by summed truncated cone volume via circumferential tape measurements. Wilcoxon signed rank test and Spearman co-relation test was used for analysis. Significant difference between the limb volumes was noted (p=0.02) and a reduction in overall upper extremity ranges was seen (p<0.05). A positive significant co-relation between pain and TSK score (r= 0.300, p=0.026) was observed.